Monitoring Strategy and Evaluation of Education and Training Program with The CIPP Method - Suharno Suharno; Pardiman Pardiman; Djony Harijanto; Ali Ashar (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This study aims to evaluate apprenticeship education and training at PPSDM MIGAS using the CIPP method. The research method used is a qualitative descriptive method where data is obtained from interviews, documentation, and photos. Respondents who are the source of data are managers, teachers, and participants in education and apprenticeship at PPSDM MIGAS Cepu. The result of this research is to evaluate from the aspect of the context of education and training which contains the background, goals, and objectives that have been implemented by the objectives, the input aspect consisting of curriculum, human resources, infrastructure, and education financing. programs and training have been carried out by the existing curriculum and with competent managers and instructors. The process aspect consisting of preparation and evaluation of the results of education and training programs has been carried out well. product aspect (outcome) which consists of the quality of participants' learning outcomes and the number of graduates participating in the training program according to their achievements.